Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Let $A$ and $B$ be normal subgroups of a group $G$ such that $A \cap B = \langle e \rangle$ and $AB = G$. Prove that $A \times B \cong G$

Attempted proof:

Define $f : A \times B \rightarrow G$ by $f(a,b) = ab$. From a proof of another exercise, the hypothesis of this problem implies $ab = ba$. Therefore, $f(a,b) = f(b,a)$.

Since $f((a,b) \cdot (c,d)) = f(ac, bd) = (ac)(bd) = a(cb)d = a(bc)d = (ab)(cd) = f(ac) f(bd)$ for $a,c \in A$ and $b,d \in B$, it follows that $f$ is a homomorphism.

Now I need to show that $f$ is bijective (so show both injectivity and surjectivity of $f$), so that $f$ is an isomorphism from $A \times B$ to $G$.

Am I on the right track?

share|cite|improve this question
Should be $f(ab, cd) = ab \cdot cd = f(a, b) \cdot f(c, d)$. Everything else sounds ok – dani_s Feb 26 '14 at 8:33
Fixed the error. My bad. – Cookie Feb 26 '14 at 8:34
Ops I meant $f(a, c) \cdot f(b, d)$. I guess you are assuming $a, b \in A$ and $c, d \in B$ – dani_s Feb 26 '14 at 8:36
Yes, that too ($a,b \in A$ and $c,d \in B$). – Cookie Feb 26 '14 at 8:39
What do you mean by "the hypothesis of this problem implies $ab=ba$"? The group certainly does not have to be abelian. Also $f(a,b)=f(b,a)$ doesn't mean anything, since $f$ is defined on $A\times B$, not on $B\times A$. And again, $f(ac)$ is even worse, since $f$ is a map of two elements, not one. – Christoph Feb 26 '14 at 8:41

Hints: You will need $AB=G$ to prove surjectivity and $A\cap B=\{e\}$ to prove injectivity.

Since you still didn't fix the issue with $f(b,a)$ and $f(ac)$ being meaningless expressions, let me elaborate on this:

You want a homomorphism $f:A\times B\to G$, so you can put a pair $(a,b)\in A\times B$ in $f$ an get some element $f(a,b)\in G$.

  • Writing $f(b,a)$ for $b\in B, a\in A$ implies you could put a pair $(b, a)\in(B\times A)$ in $f$, which is not the case, since $f:A\times B \to G$, $\color{red}{\text{not }f:B\times A\to G}$.
  • Writing $f(ac)$ for $a,c\in A$, thus $ac\in A$, implies you could just put an element of $A$ in $f$, which is not the case, since $f:A\times B\to G$, $\color{red}{\text{not }f:A\to G}$.

What you want is for $(a,b), (c,d) \in A\times B$ to have $$ f((a,b)\cdot(c,d)) = f(a,b)\cdot f(c,d),$$ where by definition of the operation in $A\times B$ we have $(a,b)\cdot(c,d)=(ac,bd)\in A\times B$. Now you suggest to define $f$ as \begin{align} f : A\times B &\longrightarrow G, \\ (a,b) &\longmapsto ab. \end{align} Using this definition, we can evaluate both sides of the equation we want to prove for $f$ to be a homomorphism: \begin{align} f((a,b)\cdot(c,d)) &= f(ac, bd) = acbd, \\ f(a,b)\cdot f(c,d) &= ab\cdot cd = abcd. \end{align} Now, since $c\in A$, $b\in B$ where $A,B$ are normal in $G$ and $A\cap B=\{e\}$ you conclude from your previous problem that $$ acbd = a(cb)d = a(bc)d = abcd. $$ Put everything together and you obtain \begin{align} f((a,b)\cdot(c,d)) &= f(ac, bd) = acbd = a(cb)d \\&= a(bc)d = abcd = ab\cdot cd = f(a,b)\cdot f(c,d). \end{align}

share|cite|improve this answer
he didn't ask for hints... – dani_s Feb 26 '14 at 8:50
@dani_s I'm still working this problem out on paper, so actually, hints like this one are helpful. :) – Cookie Feb 26 '14 at 8:53
@glacier still, if you didn't ask for hints then no hints should be given! – dani_s Feb 26 '14 at 8:56
What you have to prove is that if $f(a, b) = f(c, d)$ then $(a, b) = (c, d)$ – dani_s Feb 26 '14 at 9:15
@glacier No, because $a \in A$ and $b \in B$ doesn't imply $ab \in A \cap B$ – dani_s Feb 26 '14 at 9:38

Perhaps more succint and going the other way around (easier, imo):

$$G=AB\implies \forall\,x\in G\;\;\exists\,a_x\in A\,,\,b_x\in B\;\;s.t.\;\;x=a_xb_x$$

Now, if also $\;x=a'_x+b'_x\;,\;\;a'_x\in A\;,\;\;b'_x\in B\;$ , then we'd have that

$$a_xb_x=a'_xb'_x\implies a'^{-1}_xa_x=b'_xb_x^{-1}\in A\cap B=1\implies\;\ldots$$

and we get injectivity of $\;G\to A\times B\;$ defined by $\;x\mapsto (a_x,b_x)\;$

Surjectivity is trivial, of course.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.